O responder por exclusão em bebês nascidos pré-termo e baixo peso - Sertori, Natália Maria (Universidade Federal de São Carlos, 2017)
The responding by exclusion is defined as the immediate choice of an unknown comparison stimulus (figure or object) in front of a model stimulus also unknown. For Behavior Analysis, it is one of the processes by which children learn to relate new words to new objects or qualities, aiding in vocabulary acquisition research. Thus, for populations at risk for language development, such as babies born preterm and underweight, analyzes of the response by exclusion can serve as a basis for formulating proposals for rapid learning of new words. Such a process has been extensively investigated on an experimental basis and is based on studies generally carried out by teaching "conditional discriminations" with the model pairing technique (MTS). The arms of this study were to attest to the occurrence of the exclusion response in preterm and low birth weight infants with ages between 18 and 21 months; To verify the learning of object-object relations after a single exclusion probe and to verify the maintenance of the emergent relation (name-object) seven days after the exclusion probe. Participants were selected through contact with those responsible, as soon as the initial repertoire of the babies' overall development was surveyed. The general procedure employed three phases with the following sequence: Phase 1) selection response teaching; Teaching of auditory-visual conditional relations in baselines using defined stimuli; Probes of exclusion and learning without mask; Phase 2) teaching response to the mask; Teaching of auditory-visual conditional relations in baselines with defined stimuli with mask; Probes of exclusion, control and learning with mask; Phase 3) reexposure to the teaching of auditory-visual conditional relations in baselines with defined mask stimuli; exclusion, control and learning probes with mask and verification probe maintenance of the emergent relation (name-object), after seven days of performing the exclusion probe. The performance of each participant was analyzed according to the programmed controls for the establishment of conditional discrimination in both the teaching stages and the various probes used. All participants responded by exclusion in the procedure without mask and in sessions with mask only one participant did not respond by exclusion for an indefinite object-object relationship; The control and learning probes showed variety in the results. The overall results suggest that infants with preterm and low birth conditions responding by exclusion and that some participants in the emergence relationship verification probe showed learning for one of the name-object relationships.
The responding by exclusion exclusion in preterm and low birth graduate program in special education
Keywords: Bebês; Responder por exclusão; Psicologia; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO